Introduction to "Sixty Years of Modern Tsunami Science, Volume 1: Lessons and Progress" - Kanoglu, Utku (2022)
Twenty-three papers are included in this PAGEOPH topical issue "Sixty Years of Modern Tsunami Science, Volume I: Lessons and Progress". The papers are grouped into four categories: historical tsunami events, studies on tsunami source models and case studies, tsunami hydrodynamics, and probabilistic tsunami hazard assessment and forecasting. Papers that reflect the current state of tsunami science and research are briefly introduced.